PSVI-15 Impact of Solubility of Dietary Fiber Fed During the Pre-Farrow Period on Sow and Litter Performance in Lactation. (12th April 2022) - Martinez, Gabriela E; Rosero, David; Wilcock, Pete; van Heugten, Eric
Abstract: This study evaluated the impact of level and solubility of dietary fiber on sow and litter performance when fed during the pre-farrowing period. Sows (n = 82) were assigned by BW to a 2×2 factorial arrangement plus a control treatment (regular lactation diet; 11.30% TDF) with the following factors: 1) High soluble dietary fiber (SDF; 6.0%) and insoluble dietary fiber (IDF; 31.10%); low soluble dietary fiber levels (SDF; 4.2%) and insoluble dietary fiber levels (IDF 28.30%) and 2) supplementation level of a fiber top-dress added to the lactation feed (0.45 vs 0.90 kg). The top-dress supplements were formulated to meet target fiber levels using sugar beet pulp and wheat middlings. Sows were transferred into the farrowing house at approximately 113 (±1d) d of gestation and experimental treatments were implemented from placement until parturition. Fiber solubility and top-dress level had no effects on sow BW during the pre-farrowing period and lactation ( P > 0.05). Lactation length was unaffected by treatments ( P = 0.57). Piglet birth weight ( P = 0.35), stillborn pigs ( P = 0.76), and number of pigs born below 0.90 kg (P=0.89) did not differ between treatments. Wean weight of piglets was not different between treatments ( P = 0.84) but, insoluble fiber increased ( P = 0.04) the number of small weaned pigs (less than 3.6 kg BW) irrespective of supplementation level (2.23 vs 1.10, and 0.37, for insoluble fiber, control, and soluble fiber, respectively). Results suggests that short-term supplementation of fiber immediately prior to farrowing and fiber solubility was not an effective strategy to improve sow performance during lactation.